Manejo integrado de la mosca Anastrepha striata, Schiner 1868 en la fruta de guayaba (Psidium guajava L) - Sara Virginia, Leal Vivas (2022)
The integrated management of the fly refers to the control of insects in a systematic and planned way, avoiding damage to the guava fruit through the application of different control methods, by not carriño out the integrated management, the quality of the fruit will be affected. Due to the attack of this pest, the same one that plays a fundamental role in the economy since it causes the loss of fruit yield, its larvae cause damage to the fruit pulp by feeding on it.-The control methods that must be taken into account in integrated management are: biological control based on the use of natural enemies that reduce insect populations, mechanical control consists of collecting fallen fruits, cultural control where carry out fallow and tracking activities on the ground, ethological control is applied through the use of traps, use of pheromones and food attractants, and chemical control is applied through the use of insecticides or toxic baits, the best control method for the fly is biological and chemical control, in biological control the Anastrepha striata fly has insects that are its natural enemies, among which we can highlight parasitoids, predators, fungi, which have as their objective in this control regulate the high populations of insects, and chemical control is based on the use of toxic baits which are economical and viable, for the preparation of this method the active ingredient malathion is used, it is recommended to make the application in hours of tomorrow, the period of this control must be carried out from the beginning of the ripening stage until the harvest of the fruit.